A tunable and versatile chemogenetic near-infrared fluorescent reporter - Lina El Hajji; Benjamin Bunel; Octave Joliot; Chenge Li; Alison G. Tebo; Christine Rampon; Michel Volovitch; Evelyne Fischer; Nicolas Pietrancosta; Franck Perez; Xavier Morin; Sophie Vriz; et al. (Nature Communications)
Abstract Near-infrared (NIR) fluorescent reporters open interesting perspectives for multiplexed imaging with higher contrast and depth using less toxic light. Here, we propose nirFAST, a small (14 kDa) chemogenetic NIR fluorescent reporter, displaying higher cellular brightness compared to top-performing NIR fluorescent proteins. nirFAST binds and stabilizes the fluorescent state of synthetic cell permeant fluorogenic chromophores (so-called fluorogens), otherwise dark when free. nirFAST displays tunable NIR, far-red or red emission through change of fluorogen. nirFAST allows imaging and spectral multiplexing in live cultured mammalian cells, chicken embryo tissues and zebrafish larvae. Its suitability for stimulated emission depletion nanoscopy enabled protein imaging with subdiffraction resolution in live cells. nirFAST enabled the design of a two-color cell cycle indicator for monitoring the different phases of the cell cycle. Finally, bisection of nirFAST allowed the design of a chemically induced dimerization technology with NIR fluorescence readout, enabling the control and visualization of protein proximity.